Analisis Beban Kerja dan Studi Waktu Kerja dalam Upaya Meningkatkan Kinerja Produksi pada UMKM Sambal - Clarita, Shindy Angel; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UMKM Sambal in Surabaya produces chili sauce using semi-manual processes and still faces problems related to high workload, unstable processing time, and unbalanced task distribution. This study aims to analyze physical workload, determine standard time, and evaluate labor requirements in the production process. The methods used include Cardiovascular Load (CVL), Stopwatch Time Study, and Workload Analysis (WLA). The CVL results show that the highest level of physical fatigue occurs in the cooking process. Time study results indicate that the standard output is determined by the process with the minimum production capacity, namely the cooking process as the production bottleneck. The WLA analysis on the cooking process shows a workload exceeding 100%, indicating an overload condition. Therefore, this study recommends optimizing task allocation and improving labor utilization to enhance productivity, efficiency, and production stability.